2008
DOI: 10.1021/ja8029174
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Step Microfluidic Polymerization Reactions Conducted in Droplets: The Internal Trigger Approach

Abstract: We report the application of the "internal trigger" approach to multistep microfluidic polymerization reactions conducted in droplets, namely, polyaddition and polycondensation. We hypothesized and experimentally established that heat generated in an exothermic free radical polymerization of an acrylate monomer (Reaction 1) triggers the polycondensation of the urethane oligomer (Reaction 2). Completion of two microfluidic polymerization reactions led to the continuous synthesis of polymer particles with an int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(63 citation statements)
references
References 61 publications
0
63
0
Order By: Relevance
“…Polymerization in UV initiated droplets is so fast that the phase separation process should be different compared to a thermally initiated polymerization. Moreover, although the temperature locally increases in a UV initiated droplet due to the exothermic polymerization [216], this temperature should not reach 60-70 °C, which is typically the temperature used in suspension polymerization. This should theoretically influence the porous nature of the final particles since all the theory of porosity is mainly based on phase separation and solvating power of the porogen.…”
Section: Droplet Formation In Microfluidic Channelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Polymerization in UV initiated droplets is so fast that the phase separation process should be different compared to a thermally initiated polymerization. Moreover, although the temperature locally increases in a UV initiated droplet due to the exothermic polymerization [216], this temperature should not reach 60-70 °C, which is typically the temperature used in suspension polymerization. This should theoretically influence the porous nature of the final particles since all the theory of porosity is mainly based on phase separation and solvating power of the porogen.…”
Section: Droplet Formation In Microfluidic Channelsmentioning
confidence: 99%
“…The solubility parameter of the polymer was calculated to be 24 (MPa) 1/2 by the authors. Adapted from [218] In another study, Kumacheva et al [216] reported the fabrication of beads with an acrylate-urethane interpenetrating network structure. The heat generated from the photopolymerization of the acrylic crosslinker triggered the formation of a urethane network.…”
Section: Examples Of Microfluidic Particle Productionmentioning
confidence: 99%
“…Recently, particular attention has been paid to droplet-based (digital) microfluidic devices since droplets isolated in immiscible oil or air can be free from cross-contamination and dispersion [4]. Numerous droplet-based applications including protein crystallization [5,6], polymerase chain reaction (PCR) [7,8], enzyme kinetic assays [3,9], and synthesis of organic molecules or nanoparticles [10,11] have been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…The isolation of particles that tend to agglomerate or stick to surfaces has been accomplished by the encapsulation of reactions within dispersed droplets, as highlighted in Figure 3(a,b). Protein crystals (Figure 3a), [67] or other insoluble compounds such as polymers (Figure 3b), [38,39] are limited in their interaction with microchannel surfaces in the presence of an immiscible barrier between the phases. Interestingly, immiscible gas-liquid interfaces [84][85][86] have been demonstrated as possible separation techniques; micron-sized particles accumulate at the lower surface-free-energy interfaces (see Figure 3c) [87][88][89].…”
Section: Passive Particle Manipulationmentioning
confidence: 99%